Effect of Tempering Temperature on Impact Wear Behavior of 30Cr3Mo2WNi Hot-Working Die Steel - Zhang, Cheng; Li, Pu; Wei, Shizhong; You, Long; Wang, Xiaodong; Mao, Feng; Jin, Dongliang; Chen, Chong; Pan, Kunming; Luo, Cheng; Li, Jingkui (Frontiers in Materials, 2019)
Effects of tempering temperature on impact wear of 30Cr3Mo2WNi hot-working die steel are investigated by SEM, TEM, hardness, and impact wear tests. From 300 to 680°C, the hardness of the steel decreases and the impact toughness increases with increasing tempering temperature, while a secondary hardening with maximum hardness, 48.6 HRC, is achieved at 550°C. Fatigue delamination wear is the main mechanism during the impact wear, and three typical damage features are identified with different tempering temperatures. Brittle fatigue cracks are easy to occur in the steels tempered at 300°C. Ductile fatigue cracks occur at medium temperatures. Surfaces of steel tempered are extruded at 680°C.